Otoritas Pengawasan Perbankan Syariah Di Indonesia - Kalsum, Ummi (Institut Agama Islam Negeri Kendari, 2018)
Authority Supervision Banking Sharia in Indonesia to study on a critical aboutsupervision banking sharia from side juridical normative. Settings and supervisionbanking sharia based on Law Number 3 of 2004 concerning Changes the Law Number 23 of 1999 concerning Bank Indonesia and Law No. 21 of 2008 are the authority of BI. Post the enactment of Law No. 21 of 2011 concerning FSA then supervision banking the original sharia to be BI's authority to switch to OJK. With so, the institution Settings and development banking sharia too switch from BI to the OJK, Committee Banking Sharia (KPS) and changed by the OJK and expanded to be Committee Development Services Finance Sharia (KPJKS). For that needed cooperation good coordination between BI and OJK. While supervision from sharia permanent is do by DSN-MUI and in LKS level is DPS as extension hands of DSN-MUI. Because fatwas issued DSN-MUI fixed applies and regulations issued by the BI good PBI and SEBI be fixed to be umbrella law supervision of Islamic banks by DPS anyway applies .